Endocrine disrupting mechanisms and effects of pesticides - Anlar Hatice Gül; Bacanli Merve; Başaran Nurşen (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2021)
Pesticides are important agents that are intentionally introduced into the environment to control various pests and disease carriers, often by killing them. Although pesticides have many important objectives, including protection against crop loss and vector-borne diseases, there are significant concerns over the potential toxicity of pesticides on various organisms, including humans. The frequent use of pesticides in agriculture has led to the long-term exposure of humans to different pesticide residues. Exposure to pesticides has been linked to disturbances in the endocrine system of animals and humans. There are increasing data on the relation between lipophilic pesticides with low biodegradability and changes in reproductive functions and parameters of male and female animals. But more epidemiological and detailed information is necessary on the probability and strength of pesticide exposure-outcome relations regarding endocrine-disrupting effects.